The Effectiveness of Acceptance and Commitment Therapy on Depression, Alexithymia and Hypertension in Patients with Coronary Heart Disease - Rahnama Zadeh, Mojtaba; Ashayerih, Hassan; Ranjbaripour, Tahere; Kakavand, Alireza; Meschi, Farahnaz (International Clinical Neuroscience Journal, 2022)
Background: According to recent studies, cardiovascular diseases have been the most prevalent cause of death and disability worldwide, one of the most hidden types of which is coronary heart disease. Coronary heart disease is mainly psychosomatic in nature and the role of psychological (especially personality) and social factors in its occurrence is very important. We aimed to evaluate the effectiveness of acceptance and commitment therapy (ACT) on depression, alexithymia, and hypertension in patients with cardiovascular diseases. Methods: The was a quasi-experimental study with a pretest-posttest design, with a control group and baseline assessment after intervention and three-month follow-up. The statistical population included all patients with cardiovascular diseases referred to Imam Reza hospital in Amol city from July to December 2020. 24 patients were selected as the sample using purposeful sampling and assigned to equal experimental and control groups randomly. The study tools were a researcher-made demographic questionnaire (2019), Toronto Alexithymia Scale (1994), Beck Depression Inventory (1990), and acceptance and commitment treatment protocol (Hayes, 2012). Data were analyzed by repeated measures analysis of variance. Results: We found that ACT had a significant effect on reducing depression, alexithymia, and hypertension. Conclusion: Patients who participated in ACT sessions had lower rates of depression, alexithymia, and hypertension.